Randomized Controlled Study to Evaluate Prophylactic Properties of Ayurvedic Treatment Protocol in Refractory and Chronic Migraine Patients - Prakash, Vaidya Balendu; Chandurkar, Nitin; Prakash, Vaidya Shikha; Sharma, Shakshi; Tiwari, Sneha (International Journal of Innovative Research in Medical Science, 2021)
Background: Migraine is a disorder marked by recurrent episodes of headache. There is a subset of migraine patients who remain refractory to the conventional prophylactic and abortive therapies. This study aimed to assess the therapeutic role of an ayurvedic treatment protocol in patients who had chronic/ refractory migraine. Methods: This single-center, open label, randomized, controlled clinical trial compared the efficacy of ayurvedic treatment protocol to conventional treatment. Included patients were 18-65 years of age and met the diagnostic criteria for chronic/ refractory migraine. The patients were randomized in a 1:1 ratio to the ayurvedic treatment or conventional therapy at the baseline and were followed at regular intervals for 360 days. The primary outcome was reduction in the number of headache days in the last 3 months and the secondary outcomes were a reduction in the visual analog scale (VAS) score and migraine disability assessment score (MIDAS) as compared to the baseline. Results: Patients (n=154) were randomized to the two treatment groups with similar baseline demographic and clinical characteristics. The patients in ayurvedic treatment group had a greater reduction in the number of headache days, VAS score and MIDAS score at day 360 (p<0.05). Further, there were no reported medication-related adverse effects in either group. Conclusion: Ayurvedic treatment protocol is well tolerated and is associated with significant improvement in symptoms of chronic refractory migraine.